Development of an EFL Curriculum Components to Promote Intercultural Communicative Competence for Chinese College Students - Li, Yue; Chookhampaeng, Chowwalit; Chano, Jiraporn; Deng, Xiaoyan (International Journal of Language Education, 2023)
This study aims to develop a curriculum based on production-oriented approach (POA) and third space theory to enhance intercultural communicative competence for college students and study the results of the implementation. Intercultural Competence Test (ICT) was administered to collect data. A total of 35 respondents were recruited from Nanfang College, Guangzhou, China. Descriptive statistics were applied to test any significant difference between pretest and post-test. The results showed that the respondents in the participating curriculum demonstrated preferences for certain strategies and significant differences were founded between pre-test and post-test. Yet, these findings are compromised to due to the small sample size, and a large-scale survey is needed to verify the results.